FAKTOR YANG MEMENGARUHI STRUKTUR MODAL PADA SUB SEKTOR MINYAK DAN GAS TAHUN 2020-2024 - Jessica Patricia Wijaya; Muhammad Vryzas Fadillah; Triana Anggraini (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of Profitability, Liquidity, Leverage and Business Risk variables on Capital Structure. The sample of this study includes 16 companies in the Energy Industry Sector of the Oil and Gas Sub-Sector based on multiple linear regression analysis method. The results showed that profitability, liquidity, and business risk had no significant effect on capital structure while leverage had a positive and significant effect on capital structure.